The Treat-to-Target Project in Atopic Dermatitis: One Year On - Marjolein de Bruin-Weller; Mette Deleuran; Tilo Biedermann; Robert Bissonnette; Peter Foley; Giampiero Girolomoni; Jana Hercogová; Chih-Ho Hong; Norito Katoh; Andrew Pink; Marie-Aleth Richard; Stephen Shumack; et al. (Medical Journals Sweden, 2023)
Atopic dermatitis is a chronic skin condition for which a range of systemic treatments have recently been approved. A treat-to-target strategy has been developed previously alongside an algorithm to guide the management of patients with atopic dermatitis. Here, we review the strategy and algorithm in the context of the evolving therapeutic landscape, and identify areas for further refinement and development.